ANEMIC PATIENT AT GP’S OFFICE - A. L. Vertkin; N. O. Khovasova; E. D. Laryushkina; K. I. Shamaeva (Кардиоваскулярная терапия и профилактика, 2014)
In contemporary medicine anemia is not just a decrease of hemoglobin level, but risk factor for worse outcome in vascular patients. At the same time anemia usually is not stated in the diagnosis and is not registered in statistic reports. Anemia – is always a complication that is why it always requires diagnostic algorithm to explore the underlying reason. Low hemoglobin level must be always marked by general physician. However in practice this happens just in 25% cases. Due to time deficiency at outpatient visits there is a demand for algorithm to provide GP with. This article concerns such algorithms to investigate the patients with found low hemoglobin level.